Perancangan Sistem Informasi Reservasi Laboratorium TI UIN Walisongo Berbasis Web - Mustofa, Hery; Ali, Thooriq Nur; Fauzan, Roman (Universitas Islam Negeri Walisongo Semarang, 2021)
The Information Technology Study Program Laboratory is part of the integrated Laboratory of UIN Walisongo Semarang which will be completed in 2021 with funding from the IsDB (Islamic Development Bank). With the existence of the laboratory, of course, many challenges will be faced. One of them is the mechanism for making laboratory space reservations. In this research, an information technology laboratory reservation information system will be designed using the waterfall method and a system model approach using an object oriented development model. With this approach, it produces a simple reservation information system and can assist in facilitating users in making reservations for IT laboratory space. From the test results, it is known that the interface design and functional system can run according to user expectations.